Incidental Neuroendocrine Tumor in Mesocolonic Ectopic Pancreas Discovered During Colorectal Cancer Surgery - Claro, Mateus Zapparoli; Donadio, Mauro Daniel Spina; Figueira, Marcos Gomes; Peixoto, Renata DAlpino (Archives of Clinical and Biomedical Research, 2025)
Background: Ectopic pancreas is a rare congenital anomaly, most commonly found in the stomach and duodenum, with mesocolonic involvement being exceptionally rare. While neoplastic transformation can occur, a neuroendocrine tumor (NET) arising in mesocolonic EP had not been previously reported. Case Description: We describe the case of a 51-year-old female who presented with nonspecific abdominal symptoms and was diagnosed with a moderately differentiated pT4a tubular adenocarcinoma of the descending colon. She underwent surgical resection, and histopathological examination incidentally revealed ectopic pancreatic tissue in the mesocolic fat, exhibiting an area of epithelioid proliferation. Immunohistochemistry showed strong positivity for cytokeratin AE1/AE3, chromogranin A, and synaptophysin, confirming neuroendocrine differentiation. Notably, the adjacent ectopic pancreatic islets also showed synaptophysin positivity, highlighting the relationship between the tumor and the heterotopic pancreatic tissue. Ki-67 proliferation index was <1%, classifying it as a grade 1 NET. Postoperative 68Ga-DOTATATE PET/CT ruled out distant metastasis, and the patient underwent adjuvant chemotherapy for the colorectal cancer, with ongoing surveillance. Conclusions: NETs can arise in ectopic pancreatic tissue, but their occurrence in the mesocolon had never been documented before. The case underscores the need for thorough histopathological evaluation of incidental findings during oncologic resections, and highlights the importance of considering ectopic pancreas as a potential site for neuroendocrine tumorigenesis.